Removal of hexavalent chromium from wastewater by acid-washed zero-valent aluminum. Issue 12 (8th March 2016) - Fu, Fenglian; Han, Weijiang; Cheng, Zihang; Tang, Bing
Abstract: This paper deals with the treatment of hexavalent chromium (Cr(VI)) and its removal mechanism using acid-washed zero-valent aluminum (ZVAl). The acid-washed ZVAl before and after reaction was characterized by scanning electron microscope, X-ray diffraction, and X-ray photoelectron spectroscopy. The influence factors such as ZVAl loading, acid washing time, and pH values on Cr(VI) removal were studied. Cr(VI) removal by acid-washed ZVAl was also evaluated under different humic acid and Fe 2+ concentrations. The removal of Cr(VI) was accelerated with increasing acid-washed ZVAl loadings and decreasing initial pH. The addition of humic acid inhibited the Cr(VI) removal, while Fe 2+ significantly accelerated the Cr(VI) removal. More than 98% Cr(VI) was removed from synthetic wastewater containing 20.0 mg/L Cr(VI) in 180 min by 0.4 g/L acid-washed ZVAl at initial pH 2.0. Cr(VI) removal by acid-washed ZVAl is proved by reduction, not by adsorption. The remarkable capacity of acid-washed ZVAl in removing Cr(VI) from wastewater displays its potential application in the treatment of wastewater-containing Cr(VI).